310 Impact of an Integrated Care Hub on Access for the Community to In-patient Rehabilitation: Right Place, Right Time. (16th September 2019) - O'Gorman, Millie; Wall, Triona; Naughton, Christina; Phelan, Niamh; Murphy, Catherine; Gantly, Thomas; Whyte, Caitriona; Bolger, Maggie; Brennan, Jacinta; Doyle, Marie; O'Donoghue, Alice; Harnett, PJ; et al.
Abstract: Background: The Inpatient rehabilitation service serves a population of 116, 176 of whom 17, 371 are aged 65yrs and over. Access to these units was traditionally via referral from the acute hospital sector with the minority of referrals coming from the community. Review of the existing rehabilitation pathway was undertaken and highlighted barriers of access to appropriate in-patient rehabilitation. The referral criteria were revised and an updated pathway was devised. Methods: A quantitative retrospective review of all referrals received in four timeframes, commencing 1 st July 2017 to date, was carried out. Each referral was classified into four subgroups: (1) Immediate Crisis (2) Emerging Crisis (3) Stable but Needs Optimisation (4) Stable and No in-patient Intervention required. The origin of the referral was also categorised into four subgroups: (1) Day Hospital (2) GP (3) AHP (4) Other. The Average Length of Stay (AvLoS) was calculated for, acute and community admissions, for each period breakdown. Results: We compared 1 st July 2017 to 31 st December 2017 pre-establishment of the new referral pathway and the same six month period in 2018 post-establishment of the pathway. The new streamlined pathway facilitated improved access to in-patient rehabilitation from multiple sources and resulted in an increase in referrals from 25 to 79. Waiting time for admission was reduced from 37 days to 5 days. Community admissions increased from 16 to 48. There was no difference in AvLoS between the two time periods: Acute 22 & Community 17 to Acute 22.25 & Community 18. Conclusion: This work highlights the effectiveness of an improved co-ordinated referral pathway, within an integrated care hub, from community to in-patient rehabilitation beds with improved accessibility and reduced waiting times. AvLoS figures suggest that appropriate patients were admitted to the rehabilitation units. Also, it confirms the efficiency of a patient centred approach in maximising appropriate services for Right Person, Right Place, Right Time.